Soy Isoflavone Supplementation in Sow Diet Enhances Antioxidant Status and Promotes Intestinal Health of Newborn Piglets - Le Liu; Lizhu Niu; Mengmeng Xu; Qing Yu; Lixin Chen; Hongyu Deng; Wen Chen; Long Che (Animals)
This study aimed to explore the effects of dietary supplementation with soy isoflavones (SI) in the later stages of pregnancy on the antioxidant capacity of sows and intestinal health of newborn piglets. Forty sows with similar body weights and parity (average of 1–2 parity) were randomly divided into two groups (n = 20): the control group and SI group (dose: 100 mg/kg of feed). Feeding was started on day 85 of gestation and continued until farrowing. SI supplementation significantly increased the antioxidant levels in the serum of the sows and newborn piglets, placental tissue, and the intestinal tract of the piglets. This observation was indicated by a decreased activity of the oxidative stress marker malondialdehyde (MDA); increased activity of antioxidant enzymes such as superoxide dismutase, glutathione peroxidase, and catalase; and enhanced total antioxidant capacity. The organ indices of the intestine and liver and the villus height/crypt depth of the jejunum of newborn piglets significantly increased. SI supplementation activated the Nrf2 signaling pathway in the jejunum of neonatal piglets and the expression of placental antioxidant proteins, and it downregulated the expression of the Bax and Caspase 3 apoptotic proteins in the placenta and neonatal piglets. Intestinal and placental barrier integrity was strengthened. For example, ZO-1, Occludin, and Claudin 1 exhibited elevated expression. In conclusion, dietary supplementation with SI enhanced the antioxidant capacity of sows and piglets and improved the health of the placenta and intestinal tract of newborn piglets.